2005
DOI: 10.1002/dev.20093
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of infant attachment

Abstract: A strong attachment to the caregiver is critical for survival in altricial species, including humans. While some behavioral aspects of attachment have been characterized, its neurobiology has only recently received attention. Using a mammalian imprinting model, we are assessing the neural circuitry that enables infant rats to attach quickly to a caregiver, thus enhancing survival in the nest. Specifically, the hyper-functioning noradrenergic locus coeruleus (LC) enables pups to learn rapid, robust preference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 145 publications
(136 reference statements)
3
141
1
5
Order By: Relevance
“…In contrast after this sensitive period (day 10) the odor-shock pairing results in a robust odor aversion. In the sensitive period, the learning of an odor preference does not involve amygdala activation, whereas in the post-sensitive period amygdala activation is required for the learning of the odor-shock aversion (Moriceau and Sullivan, 2005). Thus a hypo-functional amygdala during infancy appears to prevent the pup from learning aversions to the caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast after this sensitive period (day 10) the odor-shock pairing results in a robust odor aversion. In the sensitive period, the learning of an odor preference does not involve amygdala activation, whereas in the post-sensitive period amygdala activation is required for the learning of the odor-shock aversion (Moriceau and Sullivan, 2005). Thus a hypo-functional amygdala during infancy appears to prevent the pup from learning aversions to the caregiver.…”
Section: Discussionmentioning
confidence: 99%
“…The neurological and endocrine bases for social motivation and affective bonding in infants (e. g., Bowlby 1969 p. 203-204;Moriceau and Sullivan 2005;Grossmann et al 2008) and children (e. g., Bartz and Hollander 2008) have been much less studied than those in mothers (e. g., Strathern et al 2009), though their relevance for understanding mother-child interactions should be no less consequential. Studies of plasma oxytocin levels in autism have yielded unusual results: two studies found lower plasma oxytocin in children with autism (Modahl et al 1998;Green et al 2001), but unexpectedly, oxytocin levels were positively associated with degree of social impairment (Modahl et al 1998); in the single study of adults, autistic individuals showed significantly higher levels of plasma oxytocin than did controls (Jansen et al 2006).…”
Section: Autism and Attachmentmentioning
confidence: 99%
“…Although various animal models have been developed to study social behaviors ubiquitous to mammalian species, including mating, maternal care, and aggression (Seay et al, 1962;Coe et al, 1978;Kendrick et al, 1992;Nelson et al, 2001;Weller et al, 2003;Levy et al, 2004;Moriceau et al, 2005;Hull et al, 2006;Hull et al, 2007;Nelson et al, 2007), the formation of strong bonds between mating pairs (pair bonding), and behaviors associated with these bonds, such as mate guarding (selective aggression) and paternal care, have been understudied, perhaps due to the lack of appropriate animal models. These behaviors are relatively uncommon in the animal kingdom, and in mammals are only displayed by the 3-5% of species that are monogamous (Kleiman, 1977).…”
Section: Introductionmentioning
confidence: 99%